THE EFFECT OF LIQUIDITY AND LEVERAGE ON COMPANY VALUE WITH PROFITABILITY AS AN INTERVENING VARIABLE - Samsi, Samsi; Indrabudiman, Amir (Univesitas Muhammadiyah Tangerang, 2024)
This research aims to examine the effect of liquidity and leverage on firm value with profitability as an intervening variable. The population of this study includes all companies in consumer Cyclicals sector listed on the Indonesia Stock Exchange (IDX) as many as 84 companies in the 2018- 2022 period. The research sampling technique was purposive sampling, and 50 companies were obtained with 250 data. The data used in this research is secondary data in the form of company financial reports obtained from the official website www.idx.co.id. The data collection technique used is documentation technique, namely by collecting data from company financial reports that have been officially recorded or published. The analytical method used is multiple linear regression analysis carried out with the help of Jamovi version 2.3.28. Based on the results of data analysis, it is concluded that liquidity has a significant negative effect on profitability, leverage has a significant positive effect on profitability, liquidity has a significant negative effect on firm value, leverage has no effect on firm value, profitability has a significant positive effect on firm value, profitability is able to mediate the effect of liquidity on Firm value and Profitability are not able to mediate the influence of Leverage on Firm value.